2004
DOI: 10.1002/adma.200306039
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Polymer Nanocomposite Morphology: AC Electric Field Manipulation of Epoxy–Montmorillonite (Clay) Suspensions

Abstract: Over the last decade, the utility of inorganic nanoparticles as additives to enhance polymer performance has been established and now provides numerous commercial opportunities, ranging from advanced aerospace systems to commodity plastics.[1] Low-volume additions (1±5 wt.-%) of highly anisotropic nanoparticles, such as layered silicates or carbon nanotubes, provide property enhancements with respect to the neat polymer that are comparable to those achieved by conventional loadings (15±40 wt.-%) of traditional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
67
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 38 publications
4
67
0
Order By: Relevance
“…[2][3][4][5][6] However, few approaches are developed to control the spatial and oriented morphology of nanomaterials when compared with the conventional ways with fiber and weaving as additives. For example, with tuning effects of electric field, epoxy-layered silicate nanocomposite, [7][8][9][10] styrene-acrylonitrile copolymer/clay nanocomposite, 11 and polypropylene/layered silicate nanocomposites 12 have been recently prepared under an applied electric field.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] However, few approaches are developed to control the spatial and oriented morphology of nanomaterials when compared with the conventional ways with fiber and weaving as additives. For example, with tuning effects of electric field, epoxy-layered silicate nanocomposite, [7][8][9][10] styrene-acrylonitrile copolymer/clay nanocomposite, 11 and polypropylene/layered silicate nanocomposites 12 have been recently prepared under an applied electric field.…”
Section: Introductionmentioning
confidence: 99%
“…Such properties are related to the volume fraction, shape and size of the filler particles. Following the pioneering work of Toyota researchers on a nylon 6-clay nanocomposite in the early 1990s [43,47,48], well-exfoliated nanocomposites have been produced in various nylons [44,[49][50][51], polystyrene [52], certain polyimides [53], polypropylene [54][55][56][57], polylactide [58,59] and epoxies [60][61][62]. These studies showed that the improvement in the mechanical performances of nanocomposites mainly originated from the nanosize dimensions of silicates (as this results in an extremely large aspect ratio) and from strong polymer-filler interactions that might affect the effectiveness of the load transfer between the silicate layers and polymer matrix.…”
Section: Mechanical Properties Of Nanocompositesmentioning
confidence: 99%
“…In addition, the degraded layered structure of nanoclay as a result of the CNTs growth within its interlayer spaces will be beneficial for future formation of exfoliated nanoclay in a polymer matrix. Compared to conventional micro-sized fillers, the addition of nanoclay and CNTs in a polymer matrix led to nanocomposite exhibiting markedly improved physicochemical properties at lower loading [22][23][24][25][26]. Since the present novel CNTs-nanoclay composite structure could be directly incorporated into a polymer matrix without the traditional removal of the support material, the resulting composite can be expected to exhibit greatly enhanced mechanical properties due to the mechanical interlocking between CNTs and nanoclay layers as well as the combination of the advantages of both CNTs and nanoclay.…”
Section: Introductionmentioning
confidence: 99%